2022
DOI: 10.1108/bfj-03-2022-0256
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting the purchase of private label products by different age consumers

Abstract: PurposeThe aim of this study is to determine how the different age of consumers impacts on some factors that drive consumers to the purchasing of private label products, considering differences and similarities of behaviors.Design/methodology/approachThe research was conducted through the administration of a questionnaire to evaluate consumers' perceptions about private label food products. To collect data, the convenience sampling method has been used. The valid answers collected and analyzed are 358.Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Different factors influence consumer choices and market outcomes in different ways. Regardless of the retailer's approach or the age of the customer base, considerations such as value for money and prior consumer happiness are important when making purchases [12] Whereas more seasoned shoppers concentrate on the provenance and traceability of items, younger consumers pay greater attention to aspects like health and instore promotions [13]. Retail grocery managers think that consumers' trust in the grocery store is the main reason for their purchase of private label brands [14].…”
Section: Private Label Success Factorsmentioning
confidence: 99%
“…Different factors influence consumer choices and market outcomes in different ways. Regardless of the retailer's approach or the age of the customer base, considerations such as value for money and prior consumer happiness are important when making purchases [12] Whereas more seasoned shoppers concentrate on the provenance and traceability of items, younger consumers pay greater attention to aspects like health and instore promotions [13]. Retail grocery managers think that consumers' trust in the grocery store is the main reason for their purchase of private label brands [14].…”
Section: Private Label Success Factorsmentioning
confidence: 99%
“…Additionally, emotional considerations (e.g., sentiments, esthetic, and epistemic emotions) at different ages provoke sensory and emotional responses, leading to a change in food interest (Zhong and Moon, 2020). Moreover, the choice is driven by factors such as familiarity with food (Gotow et al, 2018), utilitarian and hedonistic norms (Shao and Li, 2021), and injunctive and descriptive norms (Melnyk et al, 2019), and each of these aspects has been discovered to be age-dependent (Musso et al, 2022).…”
Section: Consumer Age and Attitudementioning
confidence: 99%
“…A concern in value for money, eco-friendliness of food, product quality, and traceability are more pronounced in older age customers. Younger age groups are more inclined toward factors such as promotion policies, fulfillment of the marketed benefits (health claims), and environmental consideration (Musso et al, 2022). Studies have shown that young children, adolescents, and young adults prefer instant food and are willing to try functional and convenience foods, sweets, and sugary beverages unless they are neophobic (Jezewska-Zychowicz and Plichta, 2021).…”
Section: Consumer Age and Attitudementioning
confidence: 99%
See 2 more Smart Citations